Coupled Li-P Zoning and Trace Elements of Olivine from Magmatic Ni-Cu Deposits: Implications for Postcumulus Re-Equilibration in Olivine. (2nd March 2022) - Mao, Ya-Jing; Schoneveld, Louise; Barnes, Stephen J; Williams, Morgan J; Su, Ben-Xun; Ruprecht, Philipp; Evans, Noreen J; Qin, Ke-Zhang
Abstract: Olivine is an important mineral in mafic–ultramafic rocks and records various crustal and mantle processes in basaltic magma. Generally, phosphorus (P) is immobile in olivine and its zoning tends to record magmatic processes. In contrast, lithium (Li) is one of the most mobile elements in olivine and tends to be re-distributed by postcumulus to hydrothermal processes. This study reports coupled Li-P oscillatory and sector zoning in cumulus olivine (Fo > 80 mol%) from magmatic Ni-Cu deposits in northwest China. The close to 1:1 relationship between Li + Na cation and P cation in olivine suggests P substitutes for slowly diffusing Si at the tetrahedral site and Li (Na) substitutes for Mg at the octahedral metal site. The preservation of such coupled Li-P zoning suggests that the charge-balanced–controlled substitution of Li + P 5+ for Mg 2+ Si 4+, producing a member of the Li(Fe)PO4 structure, may cause sluggish Li diffusion in olivine. The Li-P zoning is uncorrelated to other elements (Fe, Mg, Cr, Al, Ca, Ti, V, Ni, Zn, Mn, Co, and Sc). The Ca abundances in cumulus olivine are significantly depleted relative to those in volcanic olivine and modeled for olivine using the rhyolite–MELTS program, whereas the Mg, Fe, Mn, Zn, Ni, and Co contents show no signs of depletion. The Cr and Al contents in high Fo olivine are lower than those in volcanic olivine with a similar Fo value. The depletions in Ca, Cr, and Al (both divalent and trivalent cations) have been attributed to post-crystallization re-equilibration processes. We suggest that the selective Ca-Cr depletion in olivine resulted from re-equilibration between olivine and clinopyroxene–orthopyroxene–spinel–melts at the postcumulus stage, whereas the Al content variation in olivine is likely controlled by olivine–spinel (pyroxene) re-equilibration. Olivine fractionation modeling results reveal that Co content in both olivine and sulfides changes slightly during evolution, whereas the olivine Ni/Co ratio decreases dramatically from 30 (at Fo90) to 4 (Fo80). These are consistent with the variation of Ni and Co contents in olivine from sulfide-barren rocks but cannot explain the strong positive Ni-Co correlation observed in olivine from the sulfide-bearing rocks. The considerable increase in the Ni/Co ratio in olivine coexisting with the high Ni tenor sulfide compared with the slight increase of the Ni/Co ratio in olivine coexisting with moderate-low Ni tenor sulfide strongly suggests that the Ni and Co contents and Ni/Co ratio in olivine from the mineralized rocks were the results of olivine–sulfide interaction. The olivine Fe/Zn and Mn/Zn ratios show little difference between sulfide-barren and sulfide-rich rocks, but these ratios decrease considerably with the decreasing Fo values. Overall, the study suggests that elements (Ca, Cr, Al, Mg, Fe, Ni, Co, Zn, etc.) diffuse faster than P have been re-distributed in cumulus olivine by re-equilibration processes, modifying the elemental content and inter-element ratios in olivine. The characteristics of the crystallization, particularly the source recorded in cumulus olivine, may be obscured and overprinted by postcumulus processes.